impresso Text Reuse at Scale. An interface for the exploration of text reuse data in semantically enriched historical newspapers - Düring, Marten; Romanello, Matteo; Ehrmann, Maud; Beelen, Kaspar; Guido, Daniele; Deseure, Brecht; Bunout, Estelle; Keck, Jana; Apostolopoulos, Petros (Frontiers in Big Data, 2023)
Text Reuse reveals meaningful reiterations of text in large corpora. Humanities researchers use text reuse to study e.g. the posterior reception of influential texts, and to reveal evolving publication practices of historical media. This research is often supported by interactive visualisations which highlight relations and differences between text segments. In this paper, we build on earlier work in this domain. We present impresso Text Reuse at Scale, the to our knowledge first interface which integrates text reuse data with other forms of semantic enrichment to enable a versatile and scalable exploration of intertextual relations in historical newspaper corpora. The Text Reuse at Scale interface was developed as part of the impresso project and combines powerful search and filter operations with close and distant reading perspectives. We integrate text reuse data with enrichments derived from topic modeling, named entity recognition and classification, language and document type detection as well as a rich set of newspaper metadata. We report on historical research objectives and common user tasks for the analysis of historical text reuse data and present the prototype interface together with the results of a user evaluation.